Cardiac arrhythmias in the critically ill. Issue 6 (June 2018) - Kerton, Matthew; Wiggins, Jessica; Purkiss, Michael
Abstract: Arrhythmias are a common problem in the critically ill and they can have significant effects on patient outcome. They often require immediate and swift action and it is, therefore, essential that clinicians have a structured approach to the recognition and management of arrhythmias. Here, we provide a framework for the appropriate management of the more frequently encountered cardiac arrhythmias in critical care. We include the algorithms from the 2015 Resuscitation Council Guidelines for reference.